Existence of Diverse Species of Algae, Composition and Biological Activity: A Review along India’s Coastlines - Choudhury, Reshma; Sahoo, Nityananda (Pharmacognosy Reviews)
This review discusses the most recent discoveries of various species of algae (seaweeds), their bioactive composition and the bioactive properties of algal extracts found along India’s shorelines. India is the 12th position among the world’s topmost mega-biodiversity countries. There are 770 species of bio-diverse marine algae, which cover 8100 kilometers of coastline in India. Gray, red and brown algae, diatoms, dinoflagellates and euglenophytes are among the marine algae found. Secondary metabolites that are structurally and biologically active can be located in abundance in seaweeds. Amino acids, fats, vitamins, carotenoids, polypeptides, polysaccharides, proteins, glycerolipids, polyunsaturated fatty acids, pigments, polyphenols, minerals and plant growth hormones are all contained in bioactive extracts. Several marine macro and micro-algae organisms contain biogenic compounds like halogenated complexes, alcoholic contents, aldehydes and some terpenes used in various activities. The extracts have several biologic effects which include antioxidant, antimicrobial, anti-inflammatory, antibiotic, antiviral, antifouling and cytotoxic activity. Seaweed species and their environment influence the composition, quantity and medicinal properties of extracts. A diverse algae biomass can be found along India’s various coastlines.
Keywords: Algae; Bioactive extract; Therapeutic properties; Pharmaceuticals; Indian coastline